Identification of extreme weather and their correlation on soybean production in Garut regency - Ruminta, Ruminta; Wicaksono, Fiky Yulianto; Nurinnida, Annisa; Wahyudin, Agus (Kultivasi, 2023)
The phenomenon of extreme weather events as a result of the impact of climate change can cause threats to agricultural systems, including soybean (Glycine max L.). Soybean is the main source of vegetable protein, which is sensitive and vulnerable to climate change. Therefore, research has been carried out through the identification analysis of changes in extreme weather events and analyzed for their correlation with soybean crops in Garut Regency to determine the effect of extreme weather elements on soybean production. The method used in this research is descriptive quantitative, using trend analysis on extreme weather with data on extreme weather elements such as maximum rainfall, maximum temperature, minimum temperature, wet spell, dry spell, the largest wind speed, and trend analysis on soybean production and productivity. Data for the research were obtained from BUTPAAG LAPAN Garut Regency, Garut Regency Agriculture Office, and other related sources. The correlation analysis used is the Pearson correlation with a significance level of 5%. The results showed that climate change impacts extreme weather changes in the Garut Regency area, with increasing extreme weather trends. However, extreme weather changes were not significantly correlated with soybean production. In this research, only the maximum rainfall and the largest wind speed were significantly correlated with soybean productivity.Keywords: correlation analysis, trend analysis, extreme weather, Garut regency, soybean production.